The European Stroke Organisation Guidelines: a standard operating procedure: - Ntaios, George; Steiner, Thorsten (International journal of stroke, 2015)
In 2008, the recently founded European Stroke Organisation published its guidelines for the management of ischemic stroke and transient ischemic attack.
Gesehen am 17.06.2020